Effects of offshore tuna farming on benthic assemblages in the Eastern Mediterranean - M Moraitis (Inter-Research, 2013)
The spatial effects of 2 tuna farms on the benthic community were investigated in the Eastern Mediterranean during the fattening period. The impact on benthic fauna was assessed in the vicinity of the fish farms (beneath and at various distances from the cages) using a variety of benthic indicators used for the implementation of the EU Water Framework Directive (WFD). There was a general consensus that most of the samples (95%) were acceptable, i.e. of ‘good’ or ‘high’ ecological status. The biotic indices were also compared between 2 different mesh sizes, total (resulting from the sum of the fractions of 1 and 0.5 mm mesh fractions) and 1 mm mesh, in order to assess the variability of the results. The indicators showed the same pattern between the 2 different sieve mesh sizes. The variability in the ecological status assigned by each indicator was also examined among the replicates taken from each station. Our results showed that one replicate is not sufficient for monitoring purposes and we suggest obtaining more replicates, while using indicators requiring less taxonomic effort for sample processing. Neither fish farms had a significant impact on benthic communities, due mainly to the exposed nature of the study site.